On economic sociology as an interdisciplinary field to know - Reyes Pedreros, Maritza Yaneth (Sociedad y Economía, 2010)
The relations between Economy and Sociology have been relatively distant, due to biggest distinguishes. ¿It is possible the existence of an interdisciplinary fieldwork between two disciplines with a few intellectual links? This text proposes to show Economic Sociology as an interdisciplinary possibility that treat to integrate twice rival knowledge to offer wealth in a moment of revival.